Severe hyperandrogenemia in postmenopausal woman as a presentation of ovarian hyperthecosis. Case report and mini review of the literature. (2nd November 2017) - Czyzyk, Adam; Latacz, Justyna; Filipowicz, Dorota; Podfigurna, Agnieszka; Moszynski, Rafal; Jasinski, Piotr; Sajdak, Stefan; Gaca, Michal; Genazzani, Andrea R; Meczekalski, Blazej
Abstract: Ovarian hyperthecosis (OH) is characterized by the presence of abundant luteinized theca cells in ovaries that secret androgen. It typically presents as severe hyperandrogenism and/or virilization in postmenopausal woman. Here we describe a 66-year old woman with presentation of severe hirsutism, alopecia, clitoromegaly and laboratory finding of significantly elevated serum total testosterone concentration and hyperinsulinemia. Performed imaging studies revealed normal sized, homogeneous ovaries, signs of endometrial hypertrophy and normal adrenal glands. Due to severe hyperandrogenemia and signs of endometrial hypertrophy, the total abdominal hysterectomy with bilateral salpingo-oophorectomy has been performed. Pathological examination revealed OH and endometrial hyperplasia. Androgenic activity of ovarian stromal cells has been confirmed using alpha-inhibin histochemical staining. Postmenopausal hyperandrogenemia is a diagnostic and therapeutic challenge and the imaging studies often may be misleading and require careful and critical consideration.